Musculoskeletal Symptoms, Work Ability, and Disability among Nursing Personnel - Ana Cláudia de Souza; Neusa Maria Costa Alexandre (2012)
Nursing personnel are at risk for developing musculoskeletal symptoms, which can result in persistent pain and inability to work. This study was designed to investigate the occurrence of musculoskeletal symptoms and their association with work role as well as to verify the relationship between pain intensity and disability among symptomatic individuals. Three hundred one nursing personnel, of whom 80.7% had musculoskeletal symptoms in at least one body part, participated in the study. The mean work ability score of symptomatic personnel was lower for physical demands. A significant difference between symptomatic and asymptomatic personnel was found for each demand measured by the Work Role Functioning Questionnaire, except social demand. Correlations were moderate but significant between pain intensity and disability. The results suggest that musculoskeletal symptoms interfere with work life.